General Synthesis of 3, 4‐Dinitrophenyl α‐Glycopyranosides. Issue 39 (21st October 2019) - Wallace, Michael D.; Stubbs, Keith A.
Abstract: A generalised simple method for the synthesis of 3, 4‐dinitrophenyl α‐glycosides is described. The nucleophilic aromatic substitution of 1‐fluoro‐3, 4‐dinitrobenzene can be achieved with a suite of partially protected sugar hemiacetals, under basic conditions. Abstract : Chromogenic substrates have been used extensively to study glycoside hydrolases, therefore simple and general methods to access these useful materials is desired. A simple synthetic methodology to access a relatively underused aryl glycoside is presented.